Clinical Utility of Melatonin in Fibromyalgia Diagnosis (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Fibromyalgia syndrome (FMS) is a chronic disease with an unknown etiology, which is characterized by reduced pain threshold (hyperallgesia) & pain with normally innocuous stimuli (allodynia).This diffuse pain is often disease associated  with wide range of  other symptoms including fatigue, sleep disturbance, stiffness& more.FMS often occur concomitantly  with other rheumatologic disease such as rheumatoid arthritis(RA), systemic lupus erthymatosus(SLE).       The pineal hormone melatonin (MT) exerts a variety of effects on the immune system. MT activates immune cells and enhances inflammatory cytokine and nitric oxide production.Methods: We were studied 75 subjects, 55 of subjects were FMS patients defined by the American Colleague of Rheumatology (ACR 2010) criteria. Patients' mean age was 32.5 ± 13.9 years. They were classified into two groups: Group I of 25  primary FMS patients . Group II of 30 secondary FMS patients with other rheumatologic disease such as RA, SLE. Twenty age and sex matched healthy individuals were included in the study as a control group.Results:Mean Melatonin titers were significantly reduced (p